f(3)=3*3-6

Simple and best practice solution for f(3)=3*3-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for f(3)=3*3-6 equation:


Simplifying
f(3) = 3 * 3 + -6

Reorder the terms for easier multiplication:
3f = 3 * 3 + -6

Multiply 3 * 3
3f = 9 + -6

Combine like terms: 9 + -6 = 3
3f = 3

Solving
3f = 3

Solving for variable 'f'.

Move all terms containing f to the left, all other terms to the right.

Divide each side by '3'.
f = 1

Simplifying
f = 1

See similar equations:

| 0.6+5=-0.3x+14 | | 2x+80=120 | | f(2)=3*2-6 | | 120+90+45+45+x=360 | | f(1)=3*1-6 | | x=3*4*8-x | | 2(3x-11)=4(2-x) | | x=2*5*8-x | | x+y+x+x-y=180 | | 2x(2x+y-4)-4xsq= | | (6-2i)+(-6+2i)= | | x=3*5*8-x | | 3c^2+23c-8=0 | | 10b-2c=1b-1c | | n+9+6= | | x.x=(x+1).(x-5/9) | | 6y+.11=7y+.56 | | 5x(x-2)+3(2x+6)= | | 12y^3+5y^2-2y=0 | | y=5*5-x*y | | -4.9t^2-9t+600=0 | | log(1.9)= | | X+5=(6x+6) | | x^2-24x+144-y^2=0 | | 3(7x-5)-4(3x-10)=8x+4 | | -4.9t^2+9t+600=0 | | 8x+-15=3x+5 | | 8x-1=3x+5 | | ((4x)2-8x+7)(5x+2)= | | 2xsq+x(5x-2)= | | 6y+.8=7y+.2 | | -6x-80=x+10+3x |

Equations solver categories